Synchronic Descriptions of Old Armenian Sonorants ռ (ṙ) and ր (r). - Petrosyan, Vardan (Bulletin of Yerevan University B: Philology, 2025)
Old Armenian sonorants ռ (ṙ) and ր (r) served the function of a phoneme (= a meaningful unit) not only in middle, but also at the end of words. This view was supported by previous investigators, as well (E. Aghayan; E. Toumanyan; H. Muradyan). They excluded the possibility that the beginning of a word could be a phonological position for the sonorants ռ (ṙ) and ր (r) on the grounds that native Armenian words and old borrowings could not have started with ռ (ṙ) and ր (r). They, as a rule, acquired an augment.  Native IE word ռունգ (< *srungh-) and certain Iranian borrowings (comp. ռազմ, ռահվիրայ, ռամիկ, ռոճիկ, ռոտաստակ) were exceptions to the rule. To begin with, in the synchronic approach the classification of the phonemes does not attach any significance to the fact of whether the given phoneme appears in native or borrowed words. Moreover, the presence of a certain phoneme with a distinctive function in even several words is sufficient to recognize its status as a phoneme.  In this regard, there are all grounds to say that the sonorants ռ (ṙ) and ր (r) fully served the function of a phoneme at the beginning of a word, too. As a matter of fact, no allophonic relations could exist between them in any position. The order of the ռ (ṙ) and ր (r) sonorants in the positional forms (= morphs) of certain word roots (= main morphemes) is an indication of morphonological relations between them, hence of the existence of the () morphoneme. There are also cases of free variation relation between ռ (ṙ) and ր (r).
Keywords: phoneme; phonological position; allophone; additional distribution; free variation; morphoneme